Complete solutions manual for Zills differential equations with computer lab experiments - Wright, N. Scott (Brooks/Cole, 1998)
This text by best-selling author Dennis G. Zill provides an alternative to more traditional differential equations texts by addressing the growing influence of technology in teaching differential equations. This book will appeal to instructors who wish to integrate the computer into teaching theory and applications of differential equations. Qualitative and numerical aspects of differential equations are introduced early in the text. In this edition, computer lab experiments, projects, and writing assignments now appear in a section at the end of each chapter